Impact of glucose-6-phosphate dehydrogenase deficiency on the severity of coronary atherosclerosis in patients with acute coronary syndromes. Issue 11 (November 2021) - Sanna, Giuseppe D.; Canonico, Mario E.; Siciliano, Roberta; Guarino, Simona; Montereggi, Francesco; Ponti, Enrico; Corda, Giulia; Talanas, Giuseppe; Parodi, Guido
Abstract : Aims: The impact of glucose-6-phosphate dehydrogenase (G6PD) deficiency on coronary atherosclerosis has not been clearly investigated so far. We aimed to assess the effects of G6PD deficiency on the extent and complexity of coronary atherosclerosis in a large unselected cohort of consecutive patients with acute coronary syndromes (ACS). Methods: We studied 623 consecutive patients presenting with ACS and undergoing coronary angiography and percutaneous coronary intervention (PCI). G6PD activity was quantitatively measured in all individuals using a biochemical assay based on the G6PD/6GPD ratio in erythrocytes. Individuals were defined as deficient when the ratio was less than 0.80. The severity and complexity of coronary atherosclerosis were assessed by SYNTAX score at baseline angiography. Results: Fifty-six patients (9%) showed G6PD deficiency. Severe (i.e. enzymatic activity < 0.10) G6PD deficiency was detected in 33 (5.3%) individuals, mainly of male sex ( n = 32). Overall, the cardiovascular risk profile was similar between patients with G6PD deficiency and controls. Patients with G6PD deficiency showed similar severity and complexity of coronary atherosclerosis as compared to control patients; accordingly, the SYNTAX score (15 vs. 14.5, P = 0.90, respectively, in G6PD-deficent patients and controls), and all its components were similar between deficient individuals and controls. The only independent predictor of a SYNTAX score of more than 22 was patients' age (odds ratio 1.035, 95% confidence interval 1.018–1.051; P < 0.001). Conclusion: G6PD deficiency does not impact on the extent and complexity of coronary atherosclerosis assessed by coronary angiography in patents presenting with ACS.